Seaweeds for fertilization of agricultural crops - Løes, Anne-Kristin (2024)
This presentation was given as a pitch in the international conference Seagriculture 2024, Torshavn, Faroe islands, June 20, 2024. Results from the BlueBio co-fund projects "MariGreen" and "SeaSoil" were presented. For complete fertilization of crop plants, it may be beneficial to combine seaweed materials (containing K, Ca, Mg, S) with bone-rich materials from captured fish species (contaning N, P, Ca). Fish bone materials are currently often wasted. Such fertilisers may be suited for organic growing. Testing at NORSØK have demonstrated rapid growth effects of fish materials and a significant long-term effect of seaweeed materials. Seaweed application should be restricted to agronomically sound rates to avoid accumulation of arsenic in the soil and imbalance in feed mineral composition. Excess uptake of K can lead to deficiency in Mg+Ca and risk of tetany in ruminants.